Characteristics and clinical outcomes of patients with Candida bloodstream infections in a tertiary care hospital in Jordan - Mera Ababneh; Ola Ali Abu-Bdair; Nizar Mhaidat; Basima Abdalla Almomani (Journal of Infection in Developing Countries)
Introduction: Candida species are important causes of bloodstream infections, accounting for significant morbidity and mortality in hospitalized patients.